Training-related changes in the EMG-moment relationship during isometric contractions: Further evidence of improved control of muscle activation in strength-trained men? - Amarantini, D.; Bru, B. (Journal of Electromyography and Kinesiology, 2015)
The possibility of using electromyography (EMG) to track muscle activity has raised the question of its relationship with the effort exerted by the muscles around the joints. However, the EMG-moment relationship is yet to be fully defined, and increasing knowledge of this topic could contribute to research in motor control and to the development of EMG-based algorithms and devices. With regards the training-related adaptations at the peripheral and central level, the present study investigated the effect of strength training on EMG-moment relationship. Our aim was to clarify its nature and gain further understanding of how morphological and neural factors may affect its form. The EMG-moment relationship was determined during knee flexion and extension isometric contractions performed by strength-trained male athletes and untrained male participants. The results showed that strength training induced linearity of the EMG-moment relationship concomitantly with enhanced maximum force production capacity and decreased co-activation of knee agonist-antagonist muscle pair. These results clarified discordant results regarding the linear or curved nature of the EMG-moment in isometric conditions and suggested that the remarkable linearity of the EMG-moment found in trained participants could indicate improved control of muscle activation.